Impact of CPO Export Ban Policy on Cooking Oil Market Integration in Indonesia - Asrilis Boy Saban (Universitas Satya Terra Bhinneka, 2025)
The purpose of this study is to analyze the impact of the CPO export ban policy on price movements and the integration of the cooking oil market in Indonesia. The data used is secondary data. Data sourced from PIHPS Indonesia. The data were analyzed using a univariate approach and the Johansen Cointegration Test approach. The analysis results show that the price of cooking oil has fluctuated in the movement for the period before the policy. At the same time, the period after the policy indicates a stable price movement for each market level. The results of the Johansen Cointegration Test show, that there is an integrated market relationship period before the policy. Meanwhile, the period after the policy shows a relationship that is not well integrated between markets. It is concluded that the impact of the CPO export ban policy has a significant effect on the movement of cooking oil prices in Indonesia. Still, the policy does not have a significanteffect on the decline in cooking oil prices between markets. Then the policy has no impact on market integration. This means that Indonesia's CPO export ban policy is not effective against the integration of the cooking oil market in Indonesia.